Empowerment of Lobster Farmers Based on Renewable Energy in Supporting the Blue Economy in Sawarna Village, Banten Province - Reztrianti, Diajeng; Rahmawantari, Dhistianti Mei; Uyun, Aep Saepul; Hidayat, Irfan; Pratama, Muhammad Daffa; Antasti, Erico (Pascasarjana Universitas Mataram, 2024)
This Community Partnership Program (PKM) was implemented to support the empowerment of a group of lobster farmers in Sawarna Village, who face various challenges in managing their farming business. The problems faced by lobster farmer groups in the village are lack of access to stable energy and limited management knowledge, which has an impact on the sustainability of the lobster farming business. The purpose of this service is to improve the knowledge and skills of lobster farmers in business management and adopt renewable energy technology as a solution to limited energy access. The method used in this activity is the Participatory Rural Appraisal approach, which involves farmers actively through socialisation, training, technology application, mentoring, and continuous program evaluation. The results of this service showed an increase in the ability of partners in business management, digital marketing, and the application of renewable energy technology in the form of solar power systems to support cultivation operations. In addition, there was a significant improvement in the quality of management after the training, with participants showing improved financial, marketing, and operational management. The conclusion of this activity is that the application of renewable energy technology and improved management capacity through training and mentoring can successfully support the sustainability of the lobster farming business in Sawarna Village, thus helping farmers to face the environmental and economic challenges faced in the long term.